Extraction solvents’ influence on the content of bioactive compounds and antioxidant activity of pansies - Ramalhosa, Elsa (2019)
Introduction: Pansies (Viola×wittrockiana) are a rich source of natural antioxidants with beneficial effects on human health. Objetives: The aim of our study was to investigate solvents’ influence (water, methanol, water:acetone (6:4, v/v)) on the extraction of bioactive compounds and antioxidant activity of pansies extracts. Methods: The bioactive compounds analyzed were the following: flavonoids, hydrolysable tannins and monomeric anthocyanins, as well as total phenols by the total reducing capacity assay (TRC). The antioxidant activity was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and reducing power assays. A Principal Component Analysis (PCA) was performed to differentiate pansies extracts. Results: The solvents that yielded extracts with the highest contents of hydrolysable tannins and TRC were methanol and water:acetone (6:4, v/v). To extract the highest contents of monomeric anthocyanins, methanol should be used (5.93 mg Cy 3-glu/g flower, d.w), while for flavonoids, water:acetone (6:4, v/v) was the preferred yielding an extract with 115 mg QE/g flower d.w. Water turned out to be the least effective solvent, giving extracts with the lowest antioxidant activity. In addition, methanol or water:acetone extracts were clearly distinguished from aqueous ones through a PCA analysis. Conclusions: Our results show that the bioactive compounds and antioxidant activity of pansies’ extracts are affected by the solvent used.